Targeting the Plasmodium falciparum proteome and organelles for potential antimalarial drug candidates. Issue 8 (August 2022) - Abugri, James; Ayariga, Joseph; Sunwiale, Samuel Sunyazi; Wezena, Cletus Adiyaga; Gyamfi, Julien Agyemang; Adu-Frimpong, Michael; Agongo, Godfred; Dongdem, Julius Tieroyaare; Abugri, Daniel; Dinko, Bismarck
Abstract: There is an unmet need to unearth alternative treatment options for malaria, wherein this quest is more pressing in recent times due to high morbidity and mortality data arising mostly from the endemic countries coupled with partial diversion of attention from the disease in view of the SARS-Cov-2 pandemic. Available therapeutic options for malaria have been severely threatened with the emergence of resistance to almost all the antimalarial drugs by the Plasmodium falciparum parasite in humans, which is a worrying situation. Artemisinin combination therapies (ACT) that have so far been the mainstay of malaria have encountered resistance by malaria parasite in South East Asia, which is regarded as a notorious ground zero for the emergence of resistance to antimalarial drugs. This review analyzes a few key druggable targets for the parasite and the potential of specific inhibitors to mitigate the emerging antimalarial drug resistance problem by providing a concise assessment of the essential proteins of the malaria parasite that could serve as targets. Moreover, this work provides a summary of the advances made in malaria parasite biology and the potential to leverage these findings for antimalarial drug production. Abstract : Malaria; Proteases; Plasmodium rhomboids ; Dipeptidyl aminopeptidases; Apical membrane antigen; Subtilisin-like proteins; Glucose transporters; Schizogony; Plasmepsins.